Modelling the spot prices of various coffee types (2001)
We investigate long-run relationships among the spot prices of four coffee types. Two cointegrating vectors emerge: one between the prices of Arabica coffee varieties, and the other one between Unwashed Arabicas and Robusta. A persistence profile analysis shows a more rapid adjustment to equilibrium for the first compared to the second vector due to the fact that the former involves the Arabica coffees, which are more homogeneous. Adjustment is relatively fast, implying that economic forces act rapidly and discrepancies in the equilibrium relationships are short-lived. We also find evidence of non-linear adjustment back to equilibrium; when prices are too high, adjustment takes place at a slower rate than when they are too low. © 2001 Elsevier Science B.V.